2020
DOI: 10.3390/ijms22010189
|View full text |Cite
|
Sign up to set email alerts
|

Is There Justification to Treat Neurodegenerative Disorders by Repurposing Drugs? The Case of Alzheimer’s Disease, Lithium, and Autophagy

Abstract: Lithium is the prototype mood-stabilizer used for acute and long-term treatment of bipolar disorder. Cumulated translational research of lithium indicated the drug’s neuroprotective characteristics and, thereby, has raised the option of repurposing it as a drug for neurodegenerative diseases. Lithium’s neuroprotective properties rely on its modulation of homeostatic mechanisms such as inflammation, mitochondrial function, oxidative stress, autophagy, and apoptosis. This myriad of intracellular responses are, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 154 publications
0
29
0
5
Order By: Relevance
“…In the context of AD, impaired autophagy is thought to be responsible in major part for the accumulation of Aβ and Tau aggregates [ 50 , 52 ]. Not surprising, drugs that activate autophagy have been found to be neuroprotective in cell culture and mouse models of AD [ 172 , 219 , 220 , 221 ]. GSK3 is a well-established inhibitor of autophagy and some studies have shown that inhibitors of GSK3 reduce AD pathology by stimulating autophagy [ 172 , 173 ].…”
Section: The Enzymesmentioning
confidence: 99%
“…In the context of AD, impaired autophagy is thought to be responsible in major part for the accumulation of Aβ and Tau aggregates [ 50 , 52 ]. Not surprising, drugs that activate autophagy have been found to be neuroprotective in cell culture and mouse models of AD [ 172 , 219 , 220 , 221 ]. GSK3 is a well-established inhibitor of autophagy and some studies have shown that inhibitors of GSK3 reduce AD pathology by stimulating autophagy [ 172 , 173 ].…”
Section: The Enzymesmentioning
confidence: 99%
“…Additionally, highly dynamic calcium fluctuations happen inside neurons, requiring their steady buffering capacity [ 16 ]. It has recently been suggested that aberrant neuronal function caused by mitochondrial dysfunction may be ameliorated either by ROS scavenging or by enhancing mitophagy [ 17 , 18 , 19 , 20 , 21 ]. Due to the postmitotic nature and metabolic dependence on mitochondria, insufficient or dysregulated mitophagy is detrimental to neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Another study was discontinued after 16-36 weeks of treatment due to the vulnerability of the elderly patients to lithium side effects (Macdonald et al, 2008). Studies of lithium treatment in animal models of AD produced important therapeutic data that has been well summarized elsewhere (Morris and Berk, 2016;Kerr et al, 2018;Damri et al, 2020). Taken together, the clinical results suggest that long-term lithium treatment is required for a beneficial effect, and that it may be particularly effective when started in the early stages of disease.…”
Section: Neurodegenerative Diseases Alzheimer's Disease and Other Tauopathiesmentioning
confidence: 99%
“…Taken together, the clinical results suggest that long-term lithium treatment is required for a beneficial effect, and that it may be particularly effective when started in the early stages of disease. Importantly, the use of microdose lithium may overcome the toxicity problems that have forced the discontinuation of certain previous trials (Morris and Berk, 2016;Damri et al, 2020).…”
Section: Neurodegenerative Diseases Alzheimer's Disease and Other Tauopathiesmentioning
confidence: 99%